Digital Economy and Green Behaviors in Context of Economic Vision 2030: A Case of Small and Medium Enterprises in UAE - Alhammadi, Saeed; Rahman, Syed Abidur (International Review of Management and Marketing, 2025)
Unprecedented global issues in the recent past have shifted the focus of world economies towards digitization and UAE is of no exception. This study aims to highlight how effectively SMEs have embraced digitization under the umbrella of economic Vision 2030 and what challenges they have faced during adoption. Qualitative research strategy is adopted to carry out this study. The responses have been collected from 10 SME owners and 10 government officials. Results of the study revealed that SMEs have demonstrated their important function in accomplishing the UAE’s Economic Vision 2030. Digital technologies have not just improved operational efficiency for these businesses but also helped to achieve the wider economic diversification aims of UAE. Similarly, role of digitization is also crucial in adopting the green practices by SMEs yet number of SMEs has still to materialize this aspect in true spirit. Many enterprises have shown their keen interest in adopting green practices and are also implementing one way or another. However, challenges such as high initial costs and lack of skill set hinders the implementation.